2021
DOI: 10.1038/s41536-021-00173-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of human juvenile chondrocyte-derived cell sheets for osteochondral defect treatment

Abstract: Knee cartilage does not regenerate spontaneously after injury, and a gold standard regenerative treatment algorithm has not been established. This study demonstrates preclinical safety and efficacy of scaffold-free, human juvenile cartilage-derived-chondrocyte (JCC) sheets produced from routine surgical discards using thermo-responsive cultureware. JCCs exhibit stable and high growth potential in vitro over passage 10, supporting possibilities for scale-up to mass production for commercialization. JCC sheets c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…As a unique scaffold-free platform, cell sheet tissue engineering, pioneered by Okano et al. uses temperature-responsive cultureware to produce 3D cell sheet constructs that retain endogenous cellular environments, cell matrix, receptors, and adhesive proteins, permitting spontaneous sheet adhesion to biologic surfaces without supporting materials [ [22] , [23] , [24] , [25] , [26] , [27] ]. Previous work from our group has shown that 3D MSC sheets are capable of producing hyaline-like cartilage in vitro that directly adheres to cartilage surfaces [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a unique scaffold-free platform, cell sheet tissue engineering, pioneered by Okano et al. uses temperature-responsive cultureware to produce 3D cell sheet constructs that retain endogenous cellular environments, cell matrix, receptors, and adhesive proteins, permitting spontaneous sheet adhesion to biologic surfaces without supporting materials [ [22] , [23] , [24] , [25] , [26] , [27] ]. Previous work from our group has shown that 3D MSC sheets are capable of producing hyaline-like cartilage in vitro that directly adheres to cartilage surfaces [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wasai et al (2021) have developed injectable fragments of allogeneic polydactylyderived chondrocyte sheets (PD sheets-mini), which resemble the characteristic of PD sheets and can maintain the cell viability of MCSs regardless of the clinically relevant needle gauge size to promote cartilage regenerations. Moreover, the safety of human juvenile cartilage-derived-chondrocyte sheets was proven in nude rat focal osteochondral defect models and the transplantation of chondrocyte sheets into human knee has shown efficacy in combination therapy for OA, which support the feasibility of cell sheet technique in clinical cartilage repair (Sato et al, 2019;Kondo et al, 2021). In TMJ regeneration, Vapniarsky et al (2018) formed TMJ implants using allogeneic costal chondrocytes in conjunction with a scaffold-free, selfassembling process and implanted the constructs into the artificial defects in the minipig disc's posterolateral portion.…”
Section: Application Of Artificial Ac With Scaffoldfree Strategymentioning
confidence: 85%
“…The absolute cell number in 1- and 2-layer cell sheet samples was quantified 24 h after layering using a tissue destructive method modified from previous reports [ 44 ]. Briefly, culture medium was removed, and each sample was rinsed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%